DESIGN OF SINGLE-PHASE BUCK MODE INVERTER BASED ON MODIFIED DC-DC BUCK-BOOST CONVERTER AS THE BASIC CELL - Pindhan Bhaskoro Hanendro B, M.
The Republic of Indonesia, as the largest archipelago in the world, has significant potential for renewable energy (RE) and has begun to utilize it primarily for electricity generation, especially on remote islands and in 3T regions (Tertinggal, Terdepan, Terluar or Underdeveloped, Remote, Outermost areas). The utilization of RE for electrifying remote islands and underdeveloped regions is being developed using high-voltage DC Microgrids, as RE power plants typically generate direct current (DC) electricity. Therefore, there is a critical need for inverters to convert DC electricity to alternating current (AC) for general use. Conventional inverters generally do not produce sinusoidal AC electricity, requiring additional external filters on both the input and output sides, resulting in large size, inefficiency, and high harmonic distortion. This research proposes a single-phase Buck mode (step-down) inverter based on a modified Buck-Boost converter as the basic cell, which has the advantage of producing sinusoidal AC electricity with low harmonic distortion in a smaller size. Experiment was conducted with a small-scale prototype, and the results were able to verify the advantages of the proposed single-phase inverter.